Design procedure and seismic response of low-damage self-centering precast concrete frames. Issue 166 (March 2023) - Li, Yadong; Geng, Fangfang; Ding, Youliang
Abstract: The seismic design procedure of the low-damage self-centering precast concrete (LDSCPC) frame is proposed. Its effectiveness was verified by nonlinear dynamic analysis based on the OpenSees model, and the seismic response of the LDSCPC frame was studied. The results show that the difference between the designed base shear and the average base shear obtained by nonlinear dynamic analysis is approximately 2.5%. The peak strain of the longitudinal reinforcement in each story of the beam is significantly lower than the yield strain, and the precast beam of the LDSCPC frame can meet the design requirements according to the structural reinforcement. The displacement response of the LDSCPC frame under frequent earthquakes is similar to the displacement response of the reinforcement concrete (RC) frame. Under rare earthquakes, the average of the maximum drift of the LDSCPC frame meets the code limit of 0.02 rad, and there is almost no residual displacement. The limit state of post-tensioned (PT) tendons will appear much later than the limit state of drift. The seismic vulnerability analysis results show that the metallic yield dampers of the LDSCPC frame can reduce the failure probability of IO and BR performance levels by 4.58% and 7.54%, respectively, which can effectively reduce the displacement response of the structure. Highlights: LDSCPC connections had great expansibility based on its low-damage and modular characteristics. The uniaxial LCdamper material adopting the M − θ r simplified model of metallic yield damper is developed in OpenSees. The direct displacement-based seismic design method for LDSCPC frames is feasible and effective. The metallic yield damper in LDSCPC frames can effectively reduce the displacement response of the structure. The stress level of the reinforcements in LDSCPC frames is far lower than that in RC frames.